Enhancing properties of unidirectional ramie fibers-reinforced polyester composites via alkali and oxalic acid treatments - Henny Pratiwi; Kusmono; Muhammad Waziz Wildan (Results in Engineering)
The increasing demand for sustainable and environmentally friendly materials has highlighted the need for natural fibers to reinforce composite materials. Chemical treatments of natural fibers are essential to enhance their compatibility with polymer matrices, thereby improving the overall performance of composite materials. In the present study, the ramie fibers were subjected to alkali, oxalic acid, and a combination of alkali and oxalic acid to fabricate their polyester-based composites. The unidirectional ramie fibers-reinforced polyester composites were produced by vacuum infusion method with the constant fibers content of 30 wt.%. The effect of chemical treatments on the mechanical, thermal, and morphological properties of the composites was investigated. Mechanical properties of the composites were evaluated in terms of tensile strength and tensile modulus, flexural strength and flexural modulus, interlaminar shear strength (ILSS), and impact strength. The results revealed that mechanical and thermal characteristics were improved due to a combination of alkali and oxalic acid treatments. The tensile strength, tensile modulus, flexural strength, flexural modulus, ILSS, and impact strength were found to have remarkably improved by 36.19, 22.34, 49.42, 95.71, 56.06, and 83.90 %, respectively, after the ramie fibers soaked with alkali followed by oxalic acid solution. The treatments also improved thermal stability, as evidenced by increased decomposition temperature. SEM analysis revealed increased fiber-matrix adhesion and surface roughness after chemical treatments, indicating increased interfacial bonding. The combination of alkali-oxalic acid treatment produced the best properties of the composites, so it had great potential to optimize the performance of ramie fibers-reinforced polyester composites. Additionally, it also provided insights for developing high-performance and sustainable materials for use in automotive components, construction materials, and lightweight structural applications.